Ecological Studies in the Nilgiris - Agarwal, S. C.; Madan, U. S.; Chinnamani, S.; Rege, N. D. (Indian Forester, 1961)
Ecological studies under different associations existing in the Nilgiris have been taken up with a view to determine the trends of succession under prevailing conditions and possible introduction of secondary succession as an effective means of Soil Conservation. The studies so far carried out have given some very interesting information. When shola forests are cleared herbs like bracken and Hypericum mysorense come up along with members of Compositae and Leguminosae. If the area has been infested with Cytisus scoparius, Symplocos spicata is seen to be the first tree species to appear. In some places Rhododendron nilagirica comes first in the grasslands. Amongst the grasses the first to appear are Eragrostis spp., Setaria glauca, Digitaria spp., Bothriochloa pertusa followed by either Chrysopogon zeylanicus or Pennisetum clandestinum. Both of these are subsequently replaced by Arundinella or Themeda spp. This replacement of P. clandestinum may prove to be very useful with the help of Arundinella spp. The former is very aggressive and is not liked by local cultivators as it is an effective cover for harbouring rats which spoil the potato crop. The studies are being continued.